The impact of Instagram-based e-portfolio on students’ motivation in writing - Nurul Izzah Syazwani Salman; Noraini Said (Penerbit UMS, 2024)
This study aims to investigate the impact of utilizing Instagram as a platform for creating and sharing e-portfolio on students’ motivation in the context of writing. As the digital landscape continues to advance, teachers seek innovative approaches to engage students in English classroom and enhance their language skills. Instagram, a popular social media platform known for its visual-centric nature, serves as a unique medium for showcasing and sharing individual work. The research employs a qualitative research design, combining multi-method approach, incorporating open-ended questionnaire, classroom observation, content analysis of students' e-portfolios and students’ reflection essays, to assess the motivational effects of Instagram-based e-portfolios on students. The participants of this study include a sample of students in SM St. Peter Telipok, Kota Kinabalu, Sabah. The study explores the impact of visual and interactive elements on students' motivation, self-efficacy, and overall writing performance. This study seeks to enrich and add to the existing literature on progressive teaching methods by shedding light on the motivational factors linked to the integration of Instagram-based e-portfolios. Ultimately, understanding the impact of such platforms on students' motivation in writing can inform educators and curriculum developers in designing effective and engaging strategies for enhancing writing skills in the digital age.